Research and Development of Silicon-Based Anode Materials for Lithium Ion Batteries - Dai, Ouwei (Transactions on Computer Science and Intelligent Systems Research, 2024)
Silicon, known for its high capacity, has become a key material in developing anodes for lithium-ion batteries (LIBs). However, the substantial increase in volume that silicon-based anodes undergo during the process of charging and discharging presents a significant obstacle. This expansion can lead to structural disintegration and loss of electrical conductivity. It also initiates undesirable parasitic reactions, all of which significantly reduce the cycle life of the battery. Consequently, these issues hinder the wider adoption of silicon in the commercial LIB sector. This comprehensive review synthesizes key advancements in silicon-based anode research, highlighting the latest trends and innovations. This investigation examines the intricate engineering of silicon lattices and the development of silicon-based composite materials, illuminating the advancement in the field of silicon anode technologies, encompassing hybrid materials like silicon integrated with graphite and those amalgamated with various metals. Additionally, it scrutinizes the lithium storage characteristics and the mechanisms at play in silicon/graphene and other silicon composites. The review concludes with a forward-looking exploration of the future trajectory of silicon-based materials, considering their potential for growth and integration within the field.